2017
DOI: 10.1002/anie.201707842
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Structure of Platinum Particles on Ceria In Situ for Enhancing the Catalytic Performance of Exhaust Gas Catalysts

Abstract: A dynamic structural behavior of Pt nanoparticles on the ceria surface under reducing/oxidizing conditions was found at moderate temperatures (<500 °C) and exploited to enhance the catalytic activity of Pt/CeO -based exhaust gas catalysts. Redispersion of platinum in an oxidizing atmosphere already occurred at 400 °C. A protocol with reducing pulses at 250-400 °C was applied in a subsequent step for controlled Pt-particle formation. Operando X-ray absorption spectroscopy unraveled the different extent of reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
223
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(249 citation statements)
references
References 35 publications
21
223
1
4
Order By: Relevance
“…The latter allowed to grow the Pt‐particles and manipulate the Pt dispersion and consequently the catalyst activity. This enables to fine‐tune the Pt particle size for an optimum in CO oxidation activity …”
Section: Characterization and Operando Methodology In Gas Sensing Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter allowed to grow the Pt‐particles and manipulate the Pt dispersion and consequently the catalyst activity. This enables to fine‐tune the Pt particle size for an optimum in CO oxidation activity …”
Section: Characterization and Operando Methodology In Gas Sensing Andmentioning
confidence: 99%
“…The latter allowed to grow the Pt-particles and manipulate the Pt dispersion and consequently the catalysta ctivity.T his enables to fine-tune the Pt particles ize for an optimum in CO oxidation activity. [14] Very small chemical changes occurring at the active noble metal phase during catalysis or sensing whichc annot be observedv ia conventionalX AS might be addressedw ith HERFD-XAS. [74a,b, 81] Based on hard X-rays the technique does not impose any other special requirements towards the materials to investigate.…”
Section: Characterization and Operando Methodology In Gas Sensing Andmentioning
confidence: 99%
“…Ganzler et al. reported that small Pt clusters supported on CeO 2 are much more active than atomically dispersed Pt and a size of ∼1.4 nm was reported to be optimal . The origin of the high CO oxidation activity on ceria supported Pt nanoparticles was proposed to be due to highly active sites at the Pt−CeO 2 interface.…”
Section: Introductionmentioning
confidence: 99%
“…There, the oxidation state of platinum, its dispersion, and microstructure substantially depend on the reaction mediumu sed for the catalyst treatment. [24,25,[33][34][35][36][37] Av ariety of platinum states is formed through as trongc hemical interaction with the support (SMSI effect), so that platinum can be in cationic states and in different metallicc luster species. [37][38][39][40][41][42][43][44][45] The interaction of metallic platinum particlesw ith ceria, studied in many publications,w as shown to increase the catalytic activity per platinum atom in comparison, for example, with the Pt/Al 2 O 3 catalyst.…”
Section: Introductionmentioning
confidence: 99%